Parent Involvement: Voices of Taiwanese Fathers - Hsiu-Zu, Ho; Tran, Connie N.; Ko, Chu-Ting; Phillips, Jessica M.; Boutin-Martinez, Alma; Dixon, Carol N.; Chen, Wei-Wen (International Journal about Parents in Education, 2023)
In recent decades Taiwan’s dynamic socioeconomic growth and political transformation have brought changes to a number of Chinese traditions giving rise to a more liberal middle class advocating for gender equality in Taiwanese society. Parenting responsibilities are becoming less gender-bound and fathers are becoming more involved in raising children. Studies examining parenting roles and practices in Taiwan, however, are limited. This paper provides a review of father involvement in historical and contemporary contexts in Taiwan as well as government and corporate policies that promote father involvement. Using Attride-Stirling’s thematic network model the paper presents results of thematic content analyses of structured interviews conducted with fifteen Taiwanese fathers ages (30-61 years) and education levels (high school to Master’s degree). The study addresses ways that fathers are involved in the lives of their young children. Major themes of father involvement to emerge were the importance of: 1) Being a positive role model; 2) Engagement with children in outdoor activities; 3) Education as a means to children’s socioeconomic advancement; and 4) Evolving nature of socially-constructed father roles in Taiwan. Results indicate that Taiwanese views about father involvement and engagement with children are slowly shifting from traditional beliefs associated with a patriarchal society toward more egalitarian beliefs with respect to gender roles and parenting responsibilities.